THE INFLUENCE OF CUSTOMER EXPERIENCE AND PERCEIVED SERVICE QUALITY ON CONSUMER SATISFACTION WITH PRODUCT QUALITY AS A MODERATING VARIABLE - Zunan Setiawan; Saifuddin Zuhri; Djoko Widagdo; Chevy Herli Sumerli A; Evi Sirait (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Customer satisfaction is the most important factor that companies must pay attention to so that their business is able to compete and even dominate the market. There are a number of factors that can influence customer satisfaction, including Customer Experience which is representative of internal factors and Perceived Service Quality is representative of external factors. Different from previous research, this research adds the Product Quality variable as a moderating variable. This research is quantitative research with an explanatory approach. The data used in this research is primary data distributed to 125 Gacoan noodle employees and 125 Gacoan noodle consumers spread throughout Indonesia. The collected data was analyzed using the smart PLS 3.0 analysis tool. The research results show that the respective variables Consumer Experience and Perceived Service Quality have a positive relationship and a significant influence on the Consumer Satisfication variable. Apart from that, the Product Quality variable can moderate the influence of the variables above, the results are even more significant than each direct test of each independent variable on the dependent variable in this research. Keywords: Consumer Experience, Percevied Service Quality, Consumer Satisfication, Product Quality